BOURDIEU, NEOLIBERALISME, INTELEKTUAL DAN GERAKAN SOSIAL GLOBAL - Hadiwinata, Bob Sugeng (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2006)
With the death of Pierre Bourdieu in 2002, the world has lost its mostpassionate and authoritative sociologist. Although politically Bourdieu was always on the Left, the early 1990s marked a sharp turn of his writings. Sickened by the tendency of Mitterrand's government in leaning to the Right, Bourdieu had become increasingly bolder and audacious in criticizing globalization and neoliberalism. What made him more frustrated was the fact that neoliberalism at least in France some other European countries was installed by those who claim to be socialist enthusiasts. In his last years, Bourdieu unleashed a volley of blistering attacks on conformism of both the media and intellectuals toward neoliberalism. His only hope was to contrive a global social movement This paper tries to show how important Bourdieu's critical perspective on neoliberalism in our attempt to understand the impact of globalization. It argues that Bourdieu's attack on neoliberalism and demand for a global social movement can help us to get a better understanding of globalization and antiglobalizationmovements.